Patients with Takayasu's arteritis having persistent acute-phase response usually have an increased major vessel uptake by 18F-FDG-PET/CT - ALİBAZ ÖNER, FATMA; DEDE, FUAT; TUROĞLU, HALİL TURGUT; DİRESKENELİ, RAFİ HANER; ÖNEŞ, TUNÇ (TAYLOR & FRANCIS LTD, 2015)
Objectives. Although not uniformly accepted, an increased uptake by 18F-fluorodeoxyglucose (FDG)-positron emission tomography (PET)/computed tomography (CT) in large vessels is accepted to be a sign of active disease in Takayasu's arteritis (TAK). We aimed to investigate the value of 18F-FDG-PET/CT for clinical assessment in a subset of TAK patients having a persistent acute-phase response (APR) without any signs or symptoms of clinical disease activity. Method. We studied 14 patients (mean age: 38.6 perpendicular to 13.9 years, Female/Male: 11/3, and disease duration: 5.7 +/- 5 years). Patients were clinically inactive (according to the definition of activity by Kerr et al.), while categorized as having persistent disease activity by physician's global assessment due only to APR. 18F-FDG uptake was graded using a four-point scale from grade 0 (no uptake present) to grade 3 (high grade: uptake higher than that of liver). Any uptake in major vessels with a grade >= 2 was accepted to be active. Results. Mean erythrocyte sedimentation rate was 50.8 +/- 13.2 mm/hour and mean C-reactive protein level was 28.5 +/- 22.1 mg/L. Active vasculitic lesions were observed by 18F-FDG-PET/CT in 9 of 14 (64.3%) patients. The median number of active vascular lesions was 2 (range: 1-5). A step-up treatment change was decided in 8 patients according to 18F-FDG-PET/CT results. Conclusion. We observed increased 18F-FDG uptake in the majority of TAK patients with an increased APR, but clinically silent disease. 18F-FDG-PET/CT showed the presence and localization of active inflammation in the aorta and its branches. Although specificity for observed lesions is not clear, 18F-FDG-PET/CT imaging may influence physician's assessment of clinical activity and treatment choices in TAK.
Keywords: Acute-phase response; Activity; PET; Takayasu's arteritis; POSITRON-EMISSION-TOMOGRAPHY; FDG PET-CT; DISEASE-ACTIVITY; F-18-FDG PET; FOLLOW-UP; DIAGNOSIS